1994
DOI: 10.2190/cfpb-9vgn-b8we-wu0e
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Computer-Related Attitudes of Secondary Students

Abstract: The pretest/posttest study measured the computer-related attitudes of grade eight and grade eleven students, the correlates of these attitudes, and the gains in these attitudes. The attitudes were measured along six dimensions: Anxiety, Confidence, Liking, Interest, Gender Equity, and Acceptance. The results of the study indicate that the computer-related attitudes of secondary students are positive, stable and resistant to change. Gender differences among these attitudes were found to be school dependent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
7
29
0
Order By: Relevance
“…This study replicated the results of previous studies. More than 20 years ago, the same moderate relationship between teachers' attitudes and ICT knowledge was found out by Woodrow (1994), however, the p-value was not significant in his case, while the results of this particular study suggested that the results could be generalized to the whole population (in this case, the teachers in the same school) because p was significant (see Table 3). According to the qualitative data analysis, most of the teachers were knowledgeable enough to conduct the lessons appropriately using ICT in the classrooms, and students noticed positive changes in teachers' practices.…”
Section: Knowledgesupporting
confidence: 51%
“…This study replicated the results of previous studies. More than 20 years ago, the same moderate relationship between teachers' attitudes and ICT knowledge was found out by Woodrow (1994), however, the p-value was not significant in his case, while the results of this particular study suggested that the results could be generalized to the whole population (in this case, the teachers in the same school) because p was significant (see Table 3). According to the qualitative data analysis, most of the teachers were knowledgeable enough to conduct the lessons appropriately using ICT in the classrooms, and students noticed positive changes in teachers' practices.…”
Section: Knowledgesupporting
confidence: 51%
“…The results showed that students in both the control and the Filamentality groups had positive attitudes toward ICT and its integration in the classroom, and that there were no significant differences between the two groups in terms of their attitudes. Woodrow (1994) emphasized that positive attitudes are necessary but may be insufficient to instigate ICT-related behavior. Based on our results, we cannot provide any further insights related to the relative importance of attitudes toward ICT utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, encouraging students to reflect on their learning processes, and on their feelings and perceptions, represents an important step in student empowerment and student control over learning, achievement, and performance. APPENDIX A Attitudes and Self-confidence Questionnaire 1. People managed before without computers, so computers are not necessary 2.…”
Section: Discussionmentioning
confidence: 99%